Bird Diversity and Existence at Pringtali Block: Implications for Conservation in Meru Betiri National Park, Indonesia - Mohammad Siddiq, Arif; Sulistiyowati, Hari; Aprilia Palupi, Annisaa; Firmansyah, Puji (HAYATI Journal of Biosciences, 2025)
Meru Betiri National Park (MBNP) is one of the conservation areas with an essential bird habitat in East Java. In the conservation monitoring and evaluation framework, we studied the diversity and existence of birds in the bird hotspot (Pringtali Block) as an implication for bird conservation in the MBNP. Bird observations were collected during January-February 2023 at the Pringtali Block using the point count method at six representative sites. The primary data recorded included bird species, abundance of each species, and frequency of encounters. Meanwhile, the secondary data were obtained from web queries covering bird conservation status and distribution through https://www.iucnredlist.org/. Data analysis was conducted in three stages: determining species composition, species diversity index (H'), and species existence value (Ef). The results recorded 70 bird species, consisting of 57 genera and 33 families, in the Pringtali Block of MBNP. The diversity index of birds was included in the high category (H' = 3.31). The average existence value (Ef) of the bird is 48.57 or x̄=3 s, which are included in the medium category. This reveals that birds in the Pringtali block have important structural and functional values in the MBNP ecosystem. This value also illustrates the importance of the presence of a bird species in the ecosystem and represents the uniqueness of the bird species. The birds with the highest Ef values were the Javan Hawk-eagle Nisaetus bartelsi (86.67) and White-rumped Woodpecker Meiglyptes tristis (86.67). Both species have low frequencies, are an endangered category, and are endemic to Java. Therefore, conservation efforts associated with MBNP have been successful.